Physicochemical properties of films based on bovine gelatin cross-linked with 1,4-butanediol diglycidyl ether - Martucci, Josefa Fabiana (2015)
The effectiveness of 1,4-butanediol diglycidyl ether (BDDGE) as a cross-linking agent of bovine gelatin films plasticized with D-sorbitol intended for food packaging is reported. Free-standing films were produced by casting gelatin film-forming solutions containing D-soritol 30 % (g/100 g dry gelatin) and variable amounts of BDDGE (0?3 g/100 g dry gelatin). The addition of 1 % BDDGE (g/100 g dry gelatin) positively influenced the solubility, water vapor permeability, and mechanical properties of the produced films. Water solubility decreased about 77 %; the water vapor permeability enhanced 20 %, and the stretching ability increased 11 times while the tensile strength was reduced up to 7-fold with regard to the non-cross-linked counterpart. A simple extraction procedure was applied to remove the potential un-reacted BDDGE and its hydrolysis products from BDDGE-treated gelatin films. Quantification was performed by gas chromatography combined with mass spectrometry (GC/MS), being lower than 0.25 μg/kg (below the limit of detection, 0.30 μg/L). Results suggested that water-soluble BDDGE may provide an effective cross-linking alternative to the usual aldehyde-based strategy to manufacture gelatin films with potential use as biodegradable food packaging materials.